(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
This article provides information about the use of personalized educational technologies in biology education, the content and types of personalized technologies. Also, the use of modern teaching technologies, the concept and ideas of pedagogical activities of person-oriented education, and the positive possibilities of introducing person-oriented education in biology lessons are revealed for students